Soil bacterial and fungal communities respond differently to various isothiocyanates added for biofumigation - Hu, Ping; Hollister, Emily B.; Somenahally, Anilkumar C.; Hons, Frank M.; Gentry, Terry J. (Frontiers in Microbiology, 2015)
The meals from many oilseed crops have potential for biofumigation due to their release of biocidal compounds such as isothiocyanates (ITCs). Various ITCs are known to inhibit numerous pathogens; however, much less is known about how the soil microbial community responds to the different types of ITCs released from oilseed meals (SMs). To simulate applying ITC-releasing SMs to soil, we amended soil with 1% flax SM (contains no biocidal chemicals) along with four types of ITCs (allyl, butyl, phenyl, and benzyl ITC) in order to determine their effects on soil fungal and bacterial communities in a replicated microcosm study. Microbial communities were analyzed based on the ITS region for fungi and 16S rRNA gene for bacteria using qPCR and tag-pyrosequencing with 454 GS FLX titanium technology. A dramatic decrease in fungal populations (~85% reduction) was observed after allyl ITC addition. Fungal community compositions also shifted following ITC amendments (e.g., Humicola increased in allyl and Mortierella in butyl ITC amendments). Bacterial populations were less impacted by ITCs, although there was atransient increase in the proportion of Firmicutes, related to bacteria know to be antagonistic to plant pathogens, following amendment with allyl ITC. Our results indicate that the type of ITC released from SMs can result in differential impacts on soil microorganisms. This information will aid selection and breeding of plants for biofumigation-based control of soil-borne pathogens while minimizing the impacts on non-target microorganisms.